Діджитал дипломатія як засіб здійснення публічної дипломатії в Україні - Медведська, Вікторія Юріївна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The relevance of the theses is determined by the necessity to analyze the digital diplomacy as a fundamental tool in the context of public policy production. The research stipulates the features of the digital diplomacy, especially in the context of strategic communications transition considering the pragmatic interests of Ukrainian partners. The purpose of the study is to highlight advantages and disadvantages of digital diplomacy as a key element of public diplomacy during the Russian-Ukrainian war. It is defined that, currently, there are a lot of new and prospective opportunities for development of digital diplomacy in Ukraine in the context of international relations globalization and formalization of guarantees to ensure international security.